Inlelligence and cultural differences. - Darley, John G. (Journal of Applied Psychology)
The article reviews the book "Intelligence and Cultural Differences," by Kenneth Eells, Allison Davis, Robert J. Havighurst, Vergil E. Herrick and Ralph Tyler.